(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyze the effectiveness of implementing the First In, First Out (FIFO) method in managing raw material inventory at Warehouse Roti O. Using a qualitative approach, data were collected through observation, interviews, and document analysis of warehouse records from 2022–2024. Verification of the reported 30% reduction in waste was conducted by comparing historical inventory data before and after FIFO implementation, supported by documentation from Quality Control reports and warehouse records. The results indicate that FIFO significantly minimized raw material waste, maintained product quality, and enhanced operational efficiency. Challenges such as limited storage space, recording errors, and insufficient staff understanding were identified, and improvements were achieved through regular training, digital record systems, and managerial supervision. The study highlights that the integration of FIFO with digital monitoring and quality assurance not only enhances operational effectiveness but also contributes to environmental sustainability and compliance with food safety standards. Unlike previous studies that focused only on FIFO’s operational aspects, this research emphasizes its holistic integration with technological adaptation, staff training, and sustainability practices in the bread industry. Thus, the FIFO method proves to be an effective and sustainable strategy for food inventory management.